THE EFFECTS OF SOUTH AFRICA’S MACROECONOMIC FACTORS ON YOUTH ENTREPRENEURSHIP - Asanda Fotoyi; Ronney Ncwadi (Acta Economica, 2025)
This study investigates the effects of South Africa’s macroeconomic factors on youth entrepreneurship using the Auto-Regressive Distributed Lag (ARDL) model, with quarterly data spanning from 2008Q1 to 2022Q4. The analysis reveals that macroeconomic variables, including GDP, human capital, interest rates, gross fixed capital formation, and youth unemployment influence youth entrepreneurship in both short and long runs. Notably, human capital and interest rates show significant relationships with education fostering entrepreneurship, while high interest rates constrain it. Although GDP and unemployment have positive associations with entrepreneurship, their effects are not statistically significant. The findings highlight the need for policies that prioritise youth entrepreneurship through improved education, supportive infrastructure, and alternative financing mechanisms. Such interventions could enhance youth-led entrepreneurial activities, mitigate unemployment, and promote sustainable economic growth. The study underscores the importance of targeted macroeconomic strategies to empower South African youth entrepreneurs and addresses gaps in existing literature on the economic determinants of entrepreneurship.